Strategic Responses to Disparities in Spousal Desired Fertility: Experimental Evidence from Rural Tanzania - Catalina Herrera-Almanza; Aine Seitz McCarthy (Institute of Labor Economics (IZA), 2025)
In sub-Saharan Africa, the gap in fertility preferences between men and women may influence household fertility outcomes as men usually desire more children and have more intra-household bargaining power. We estimate the effect of an informational family planning program that randomizes the inclusion of husbands on fertility preferences (desired additional children) in rural Tanzania. Surprisingly, husbands who participated in joint family planning consultations increased their desired fertility, and their wives responded by also increasing their desired number of additional children, converging to his larger preferences. In contrast, women in private family planning consultations (without their husbands) reduced their fertility desires, while their husbands' preferences remained unchanged. We provide evidence that the increase in women's fertility preferences as a result of the joint consultations is related to polygamy. Women in polygamous marriages increase their demand for children substantially, likely as a strategic response to hearing their husbands' stated preferences during the joint consultations.
Keywords: D13; J13; O15; 330; intra-household bargaining; fertility; randomized experiment; fertility preferences